2007
DOI: 10.1007/s11581-007-0109-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of ion–solvent interactions and activation energy of LiBr in DMSO, H2O and DMSO–H2O mixtures at various temperatures

Abstract: The Jones-Dole B coefficients of the electrolyte Lithium bromide (LiBr), reference salts tetra butyl ammonium tetra phenyl borate (BU 4 NBPh 4 ), tetra butyl ammonium bromide (BU 4 NBr), and potassium chloride (KCl) in dimethylsulfoxide (DMSO), water, and DMSO-water mixtures were obtained at different temperatures range from 25 to 45°C For this, the relative viscosities were measured for Lithium bromide (LiBr) and reference salts in DMSO, water, and DMSO-water mixtures at above-mentioned temperatures. The B co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
4
8
0
1
Order By: Relevance
“…It is also observed that viscosities of solutions increased with the increase of electrolyte concentration which is a common feature in most non-aqueous solvents and also in the mixture of non-aqueous solvents [15].…”
Section: Results and Disscussionmentioning
confidence: 87%
“…It is also observed that viscosities of solutions increased with the increase of electrolyte concentration which is a common feature in most non-aqueous solvents and also in the mixture of non-aqueous solvents [15].…”
Section: Results and Disscussionmentioning
confidence: 87%
“…This salt was also recovered after a set of measurements by precipitation from the DMSO solution using water. Bu 4 NBr was purified by the methods reported in our previous work . Tetrabutylammonium bromide (Aldrich) with a melting point of 103 °C was recrystallized from benzene and n -hexane.…”
Section: Methodsmentioning
confidence: 99%
“…As the temperature increased, more molecules are able to escape from the potential wells provided by their neighbors and so the solution becomes more fluid. The observed value of viscosity increased with increasing sodium acetate concentration due to the increase of the intermolecular forces which cause to resist in flow process [15]. The viscosity data has been analyzed using the JonesDole equation [16]: ( 7 ) A perusal of Table 6 shows that the values of the (A) coefficient decrease with the increase in percentage of acetone in the mixtures under study and decrease with the increase in temperature for water and increase with the increase in temperature for almost water-acetone mixtures.…”
Section: It Is Found Frommentioning
confidence: 97%